Warisan Budaya Jember: Studi Kebudayaan Kontemporer dan Simbolisme Kesenian Can Macanan Kaddhuk - Wisnu Aji; Tiara Putri Maulida; Yuzicha Nindia Safira Revizal; Adil Fihukmi Farqi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Can Macanan Kaddhuk is a traditional art typical of the Jember region, East Java. The creation of this art has become the sole meaning of Jember culture, which has its own story and has gained public legitimacy for this local culture. Events exist from the founder's subjective composition which continues to be passed down to legitimize society. This art also characterizes itself as an acculturation of several cultures around its region. So, it is very interesting that the presence of its founder at the beginning of the emergence of social culture made the beliefs dominant among each group. Moreover, the development of this culture has a very unique style, representing every art activist's interpretation. The expression of symbolic meaning and aesthetic value in the art of Can Macanan Kaddhuk requires encouragement in the post-modern world in terms of art, so the research uses a qualitative approach with appropriate methods. The results of this research show that it is not only focused on its function, namely as entertainment, but is intended as a medium for conveying the moral and spiritual messages contained therein.